SUMBER DAYA PENGELOLA TRANSPORTASI PUBLIK PERKOTAAN: STUDI BUS TRANS METRO PEKAN BARU - Raden Imam Al Hafis; Abdul Hakim (REFORMASI, 2014)
Transportation is the lifeblood of the development of an area, if an area has a good transport system and can accommodate all mobility needs of the existing community, then the area will be developed and grew rapidly both in the field of economic, social, political and territorial. It takes a good resource, be it human resources, budget resources, and facilities to support resource management in the implementation of urban public transportation. Many inadequate resources management in the implementation of urban public transport such as bus stops where the facilities are minimal. Difficulties in recruiting and retaining competent administrators, salaries, prestige and job security is low. Availability of good human resources, budget and facilities is a requirement of successful implementation and management will produce an output that is in line with expectations. For the necessary cooperation from the government to the private sector to undertake the management of urban public transport (bus of trans metro pekanbaru).